Implementasi Pembelajaran Bahasa Arab di MTs Mambaul Ulum Tulupari Tiris Probolinggo - Firdaus, Sulton; Wijaya, Mu'alim; Qomariyah, Qomariyah (AS-SABIQUN, 2024)
This research aims to explore the implementation of Arabic language learning at MTs Mambaul Ulum Tulupari Tiris Probolinggo. The focus of this research consists of three main sub-variables, namely: lesson planning, lesson implementation, and assessment or evaluation of learning. The main objective of this research is to achieve effective learning for students so that the learning process can be optimized and the average student grades can reach the Minimum Completion Criteria. The research method used is a qualitative approach using a case study method. Data were collected through observation, interviews, and analysis of documents related to the planning, implementation, and assessment of Arabic language learning. The results of this research explain that learning at MTs Mambaul Ulum Tulupari Tiris Probolinggo involves a structured planning process with clear objectives, including goal identification, material selection, method determination, assessment planning, and continuous adjustment. Its implementation focuses on meaningful learning experiences, active interaction, and the use of diverse learning methods and resources. Meanwhile, learning evaluation encompasses a holistic approach with various assessment methods, feedback, formative and summative evaluations, as well as student involvement in the evaluation process and adjustments for continuous improvement.